The Diverse Function of PD-1/PD-L Pathway Beyond Cancer - Qin, Weiting; Hu, Lipeng; Zhang, Xueli; Jiang, Shuheng; Li, Jun; Zhang, Zhigang; Wang, Xu (Frontiers in Immunology, 2019)
The recent success of PD-1 and PD-L1 blockade in cancer therapy illustrates the important role of the PD-1/PD-L1 pathway in the regulation of antitumor immune responses. However, signaling regulated by the PD-1/PD-L pathway is also associated with substantial inflammatory effects that can resemble those in autoimmune responses, chronic infection, and sepsis, consistent with the role of this pathway in balancing protective immunity and immunopathology, as well as in homeostasis and tolerance. Targeting PD-1/PD-L1 to treat cancer has shown benefits in many patients, suggesting a promising opportunity to target this pathway in autoimmune and inflammatory disorders. Here, we systematically evaluate the diverse biological functions of the PD-1/PD-L pathway in immune-mediated diseases and the relevant mechanisms that control these immune reactions.